Unpacking The Auditor's Role: The Effect of Professional Scepticism, Workload, and Work Experience in Detecting Fraud at The Inspectorate of South Sulawesi Province - Amalia, Regita; Amiruddin, Amiruddin; Bangsawan, Achdian Anggreny (LPPM Universitas Terbuka, 2025)
This research aims to find out The influence of Skepticism Professional, Workload, and Work Experience on the Auditor's Ability to Detect Fraud at the Inspectorate Office of South Sulawesi Province. The population in this study were all auditors who worked at the Inspectorate Office of South Sulawesi Province, totalling 42 auditors. Meanwhile, in selecting the sample, the researcher used the census sampling technique. This research uses a survey method by distributing questionnaires. The statistical method used to test the hypothesis is multiple linear regression. The results showed that the variables of professional scepticism, workload, and work experience had a positive and significant effect on the auditor's ability to detect fraud. The contribution of this research is to provide empirical evidence on the fectors that influence auditors effectiveness in detecting fraud, which can serve as a basis for the inspectorate in formulating policies to improve auditor competence and manage workload. Moreover, this study enriches the literature on public sector auditing, particularly in the context of government oversight at the regional level.